Why Do Some People Choose Opportunistic Rather Than Organized Cancer Screening? The Korean National Health and Nutrition Examination Survey (KNHANES) 2010-2012 - Hahm, Myung-Il; Chen, Hsueh-Fen; Miller, Thaddeus; O’Neill, Liam; Lee, Hoo-Yeon (Cancer Research and Treatment, 2017)
Although the Korean government has implemented a universal screening program for common cancers, some individuals choose to participate in opportunistic screening programs. Therefore, this study was conducted to identify factors contributing to the selection of organized versus opportunistic screening by the Korean general population. Data from 11,189 participants aged ≥ 40 yearswho participated in the fifth Korean National Health and Nutrition Examination Survey (2010-2012) were analyzed in this study. A total of 6,843 of the participants (58.6%) underwent cancer screening, of which 6,019 (51.1%) participated in organized and 824 (7.5%) participated in opportunistic screening programs. Being female, older, highly educated, in the upper quartile of income, an ex-smoker, and a light drinker as well as having supplementary private health insurance and more comorbid conditions and engaging in moderate physical activity 1-4 days per week were related to participation in both types of screening programs. Being at least a high school graduate, in the upper quartile for income, and a light drinker, as well as having more comorbid conditions and engaging in moderate physical activities 1-4 days per week had a stronger effect on those undergoing opportunistic than organized screening. The results of this study suggest that socioeconomic factors such as education and income, as well as health status factors such as health-related quality of life and number of comorbid conditions and health behaviors such as drinking and engaging in moderate physical activity 1-4 days per week had a stronger influence on participation in an opportunistic than in an organized screening program for cancer.